Vietnam labour market and informal economy in a time of crisis and recovery 2007-2009 : (Ngân hàng Thế giới (WB), 2010)
The purpose of this research is to examine the characteristics, role and impact of Vietnam’s informal sector on household living conditions. With this in mind, DIAL’s researchers in Vietnam worked upstream on improving the Vietnamese statistical apparatus with two surveys on the informal sector in Hanoi and Ho Chi Minh City (2007-2008 and 2009) and an upgrade of the labour force surveys (LFS)